Cockayne syndrome mutation in XPG activate the integrated stress response - Danhui Zhang; Max Hartmann; Zhouli Cao; Gaojie Zhu; Gregoire Najjar; Cagatay Günes; Steffen Emmert; Karin Scharffetter-Kochanek; Sebastian Iben (Human Genetics, 2026)
Xeroderma pigmentosum (XP) and Cockayne syndrome (CS) are diseases provoked by mutations in multifunctional proteins that are involved in DNA repair. DNA-repair deficiency explains the high cancer incidence of XP, whereas cancer-free CS, characterized by growth retardation, neurological degeneration, and premature aging does not present as a classical DNA-repair deficiency disorder. Here, we compared a severe combined XP/CS case provoked by XPG -mutation with an XP “only” patient cell line caused by mutation in the same XPG gene to carve out the pathogenic cellular disturbances that provoke CS. We identified RNA polymerase I transcription and rRNA maturation defects, a highly phosphorylated eukaryotic initiation factor 2 alpha (eIF2alpha), and a shift from cap- to internal ribosomal entry site (IRES) translation, indicating an activated integrated stress response in CS. Disturbances in ribosomal biogenesis and translational control might thus contribute to the development of CS.